Medicinal Plant Images - Cock, I.E. (Pharmacognosy Communications)
Aloe is a genus of approximately 400 succulent plants, many of which are native to Africa. Plants of the genus Aloe have one of the longest recorded history of medicinal usage and are amongst the most widely used plants for traditional medicinal purposes worldwide. The Aloes have been used since ancient times, particularly for the treatment of microbial infections, gastrointestinal disorders and inflammatory conditions.1 Aloe vera, Aloe ferox, Aloe arborescens and Aloe perryi are the best known and most widely used, although many other species are also used for their therapeutic properties. Despite their wide spread usage, studies from different laboratories often report wide variations in the therapeutic bioactivities from Aloe spp., with some studiers reporting potent antibacterial activity.2,3 yet other studies reporting a complete lack of activity.4 Leaves from individual plants within the same species may have widely varying levels of the bioactive phytochemicals and thus wide variances in bioactivity. Phytochemical analyses have shown that many Aloe species contain various carbohydrate polymers (notably glucomannans) and a range of other low molecular weight phenolic compounds including alkaloids, anthraquinones, anthrones, benzene and furan derivatives, chromones, coumarins, flavonoids, phytosterols, pyrans and pyrenes.1 Intra and interspecies differences in the levels and redox states of the individual Aloe components (and in the ratios of these components) may affect the physiological properties of Aloe extracts.5 Due to the structure and chemical nature of many of the Aloe phytochemicals, it is likely that many of the reported medicinal properties are due to antioxidant or prooxidant effects. The antioxidant/prooxidant activities of many Aloe spp. phytochemicals depend not only on their individual levels, but also on the ratios between the various components and their individual redox states. Therefore, discrepencies between bioactivity studies are likely when using different crude mixtures. This photograph was taken in Johannesburg, South Africa by Dr Ian Cock in December 2017.